Comparative evaluation to determine the efficacy of conventional radiography, digital radiography and ultrasound imaging in the diagnosis of periapical lesions. Issue 3 (2021) - Gupta, Rajesh; Gupta, Preety; Gupta, Shivani; Garg, Sumit
No abstract available